Factors affecting financial performance of commercial banks listed on the Vietnamese stock market - Tran, Thi Viet Thach; Vu, Ngoc Anh; Nguyen, Viet Anh (Edelweiss Applied Science and Technology, 2026)
Financial performance of banks not only reflects the health of banks but also affects the stability and development of the financial system of each country. Many previous studies have researched the factors affecting the financial performance of banks at different time periods and contexts. This article focuses on identifying the factors affecting the financial performance of commercial banks listed on the Vietnamese Stock Market in the period of 2016-2024. Based on data collected from the audited financial statements of the 20 largest listed commercial banks (measured by total assets) on the Vietnamese stock market, the study developed a quantitative research model with 179 observations from the 20 selected banks. By using the Stata software, the study selected the Feasible Generalized Least Squares Model (FGLS). The empirical results indicated that capital adequacy, operational efficiency, and economic growth impacted the financial performance of the listed commercial banks in Vietnam. The findings suggested that, to enhance financial performance, commercial banks should increase their capital and improve operational efficiency. The research results also confirmed that a period of high and stable economic growth contributes positively to the improvement of banks' financial performance.